Adaptive management: Promises and pitfalls - McLain, Rebecca J.; Lee, Robert G. (Environmental Management, 1996)
Proponents of the scientific adaptive management approach argue that it increases knowledge acquisition rates, enhances information flow among policy actors, and provides opportunities for creating shared understandings. However, evidence from efforts to implement the approach in New Brunswick, British Columbia, Canada, and the Columbia River Basin indicates that these promises have not been met. The data show that scientific adaptive management relies excessively on the use of linear systems models, discounts nonscientific forms of knowledge, and pays inadequate attention to policy processes that promote the development of shared understandings among diverse stakeholders. To be effective, new adaptive management efforts will need to incorporate knowledge from multiple sources, make use of multiple systems models, and support new forms of cooperation among stakeholders.

Appraising Adaptive Management - Lee, Kai (Conservation Ecology, 1999)
Lee, K. N. 1999. Appraising adaptive management. Conservation Ecology 3(2): 3. https://doi.org/10.5751/ES-00131-030203

Adaptive Management - Bormann, B.T.; Martin, J.R.; Wagner, F.H.; Wood, G.W.; Alegria, J. (Ecological stewardship: a common reference for ecosystem management, 1999)
Wagner
Google-Books-ID: a5vuAAAAMAAJ
Keywords: Conservation of natural resources; Ecology; Ecosystem management; Ecosystem management - United States; Environmental Science; Environmental management; Wildlife

Compass and Gyroscope: Integrating Science and Politics in the Environment - Lee, Kai N. (Island Press, 1993)
In this original and far-reaching synthesis, Kai N. Lee explains that together science and politics can lead the waytoward the sustainable management of the world’s resources. Rigorous science can act as our compass, pointingus toward greater and more useful knowledge (adaptive management), and practical politics can serve as our gyroscope, keeping usbalanced between competing interest groups. Unlike some approaches to sustainable development, Compass and Gyroscope is refreshingly grounded in the realworld. Lee explains that sustainability cannot occur overnight, we have neither an adequate base of knowledgenor a reliable means of properly implementing and executing management plans. "Sustainable development is not a goal, not a condition likely to be attained on earth as we know it. Rather it is more like freedom or justice,a direction in which we strive..." Using the Columbia River Basin in the Pacific Northwest as a case study, Lee examines the successes andfailures of past and present management. He describes what has been learned, and explains how that experiencecan be applied to environmental management generally. Throughout, the author delves deeply into the theoretical framework behind the real-world experience, exploring how theories of science, politics, and cognitive psychology can be integrated into environmental management.

Review of Development Projects as Policy Experiments: An Adaptive Approach to Development Administration - Uphoff, Norman (Economic Geography, 1985)

Development Projects as Policy Experiments: An Adaptive Approach to Development Administration - Rondinelli, Dennis A. (Methuen, 1983)
International assistance programmes for developing countries are in urgent need of revision. Continuous testing and verification is required if development activity is to cope effectively with the uncertainty and complexity of the development process. This examines the alternatives and offers an approach which focuses on strategic planning, administrative procedures that facilitate innovation, responsiveness and experimentation, and on decision-making processes that join learning with action. A useful text for academics and practitioners in development studies, geography and sociology.

The process approach to projects - ODA (Overseas Development Administration, 1989)

The principle of the hiding hand - Hirschman, Albert O. (National Observer, 1967)

Requisite Variety and Its Implications for the Control of Complex Systems - Ashby, W. Ross (Cybernetica, 1958)

Development as Process: Concepts and Methods for Working with Complexity - Mosse, David; Farrington, John; Rew, Alan (Routledge, 1998)
Process" approaches to economic and social development appear to be more flexible and offer greater prospects of success than traditional "project" methods. Development as Process addresses the questions raised by the different natures of the two approaches. The authors examine development projects through experience in water resources development in India and in organizational learning by a Bangladeshi NGO. Inter-agency contexts are examined in the setting of an aquaculture project in Bangladesh and in the setting of agriculture and natural resources development in Rajisthan, India. Finally, the role of process monitoring is explained in the context of policy reform, with illustrations from forestry in India and land reform in Russia.
Google-Books-ID: baVE8SzJkNMC
Keywords: Demography; Economic Development; Sociology

Whose Reality Counts? Putting the First Last - Chambers, Robert (ITDG Publishing, 1997)
In this sequel to "Rural Development: Putting the last first" Robert Chambers argues that central issues in development have been overlooked, and that many past errors have flowed from domination by those with power.Development professionals now need new approaches and methods forinteracting, learning and knowing. Through analyzing experience - of past mistakes and myths, and of the continuing methodological revolution of PRA (participatory rural appraisal) - the author points towards solutions.In many countries, urban and rural people alike have shown an astonishing ability to express and analyze their local, complex and diverse realities which are often at odds with the top-down realities imposed by professionals. The author argues that personal, professional and institutional change is essential if the realities of the poor are to receive greater recognition. Self-critical awareness and changes in concepts, values, methods and behaviour must be developed to explore the new high ground of participation and empowerment."Whose Reality Counts?" presents a radical challenge to all concernedwith development, whether practitioners, researchers or policy-makers, in all organizations and disciplines, and at all levels from fieldworkers to the heads of agencies. With its thrust of putting the first last it presents a new, exciting and above all practical agenda for future development which cannot be ignored.